What did they mean by that? : a dictionary of historical terms for genealogists - Drake, Paul, 1932- (Bowie, Maryland : Heritage Books, 1994)
A Dictionary of Historical Terms for Genealogists.
Includes bibliographical references.
Keywords: English language -- Obsolete words -- Dictionaries; English language -- Glossaries, vocabularies, etc; English language -- Archaisms -- Dictionaries; Genealogy -- Dictionaries; Anglais (Langue) -- Mots désuets -- Dictionnaires; Anglais (Langue) -- 1500-1700 (Moderne) -- Glossaires, vocabulaires, etc; Anglais (Langue) -- 18e siècle -- Glossaires, vocabulaires, etc; Anglais (Langue) -- Archaïsmes -- Dictionnaires; Généalogie -- Méthodologie.; Généalogie -- Dictionnaires anglais; English language; English language -- Archaisms; English language -- Obsolete words; Genealogy; Controlled vocabularies; Dictionaries; Glossaries, vocabularies, etc; Dictionaries; Controlled vocabularies